WHY CARDIOVASCULAR MORTALITY IN MOSCOW IS LOWER THAN IN OTHER REGIONS OF THE RUSSIAN FEDERATION? - N. V. Pogosova; R. G. Oganov; S. V. Suvorov (Кардиоваскулярная терапия и профилактика)
Since 2003 there is a decline of cardiovascular (CVD) mortality of the RF, that established in 2006 in women and in men. From 2003 to 2013 y. total coefficient of cardiovascular mortality (number of died per 100 thousand of population) decreased by 25% (698,1 vs. 927,5), although still it is higher than in the beginning of the nineties (621,0 per 100 thous. of population in 1991 y.). The significant differences in RG regions are noted by the values of morbidity and mortality from CVD. For the period 2006-2013 y. the standardized value of mortality from coronary heart disease (CHD) in Moscow decreased by 35,7% that is 1,5 more than in RF and 1,3 more higher than in St-Petersburg, and 2,6 times more than in Moscow region. In 2012 the value of the suspected life duration (SLD) of Moscow citizens was 76,0 y. (mean in Russia — 70,0 y), and just 4 years is the gap between then and EU citizens. In 2013 SLD in Moscow reached 72,3 y. Significantly lower values of mortality from CVD and higher values of SLD can be explained by higher socio-economic level, higher psychological endurance and better availability of psychological (psychotherapeutic) help, higher level of fish, fruits and berries consumption, better availability of outpatient and high technology medical care for Moscow citizens.